Efficacy of Yijinjing for Soft Tissue Improvement in Patients with Non-specific Chronic Neck Pain: Study Protocol for a Multicenter Randomized Controlled Trial - Fei Yao; Xiang Chen; Fangfang Xie; Min Fang; Hongyu Yue; Hanyu Zou; Zonglin Wen (BMJ Open)
Introduction As a mind–body exercise, Yijinjing has shown benefits in enhancing the effects of manual therapy for the treatment of pain, disability and soft tissue status associated with non-specific chronic neck pain (NCNP). The efficacy of Yijinjing as an independent exercise regimen for the treatment of NCNP has not been established. This study is designed to assess the efficacy of Yijinjing in patients with NCNP, compared with cervical function training (CFT).Methods and analysis A total of 132 consenting NCNP participants will be randomly assigned in a 1:1 ratio to either the Yijinjing group or the CFT group (three times a week for 8 weeks). Both groups will undergo an 8-week intervention phase. Outcome variables will be assessed at baseline and at 4-week, 8-week and 12-week follow-up. The primary outcome measure is the change in visual analogue scale scores at week 8. Secondary outcomes include neck disability index, cervical range of motion and soft tissue status parameters.Ethics and dissemination This study has been approved by an independent ethics committee and will be carried out according to the principles of the Declaration of Helsinki, local laws and regulations. The results of this study will be disseminated through presentation at scientific conferences and publication in peer-reviewed journals.Trial registration number ITMCTR2024000323.